Learning Dynamics In Economic Education: The Effect of the Joyful Learning Approach, Learning Motivation, and Teacher’s Role on Students’ Learning Outcomes at SMA Negeri 8 - Riska Dwi Rohmatika; Bayu Surindra; Elis Irmayanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study seeks to analyze the influence of the joyful learning approach, learning motivation, and the role of teachers on the learning achievement of grade X students of SMA Negeri 8 Kediri in the subject of Economics. This research is motivated by the fact that there are still students who have not achieved the Minimum Completeness Criteria (in Indonesia called KKM), so efforts are needed to identify factors that can improve learning outcomes. This research applies a quantitative analytical method with an associative design. The study sample comprised 124 students who were selected using purposive sampling techniques. A questionnaire served as the primary tool for gathering data, while multiple linear regression was processed analyzed through SPSS software. The findings showed that the joyful learning approach  contributed positively and significantly to the improvement of student learning outcomes. (t = 4.121; p < 0,05). A statistically significant positive effect was identified between learning motivation and learning outcomes. (t = 3.399; p < 0.05), along with the role of teachers which similarly demonstrated a positive and significant influence (t = 2.710; p < 0.05). Taken together, the joyful learning approach, learning motivation, and the teacher’s role had a significant influence on student learning outcomes (F = 12.252; p < 0.05). The value of the determination coefficient of 0.215 confirms that these three variables are able to explain 21.5% of the differences in student learning outcomes. These This finding shows that the joyful learning approach, high learning motivation, and optimization of the role played by teachers are decisive factors in improving students’ learning outcomes